QUALITY FOR UNDERGRADUATE EDUCATION (QUE) : THE CASE OF THE DEPARTMENT OF ECONOMICS & DEVELOPMENT STUDIES FACULTY OF ECONOMICS, GADJAH MADA UNIVERSITY - Faried Wijaya Mansoer (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
The Department of Economics and Development Studies at Gadjah Mada University’s Faculty of Economics (from hereforth referred to as DEDS-FE-GMU) sets its purpose first, to become a leading research based education center, second providing an international first-rate education in economics, and third to be at the forefront of academic institutions in the field of business economics. Accomplishment of the department’s missions requires planning and execution of several phases of improvement programs within the next five academic years. The programs are categorized into improvements in terms of educational facilities, teaching staff and education process, the quality of student output. The department plans to improve and upgrade all existing education support systems. A more modern and complete library is a necessity, with a competent staff of librarians to assist lecturers and students in obtaining data. The language lab will be enhanced with the most up-to-date teaching aids to facilitate more effective process of learning English. Lastly, the computer lab will be upgraded to incorporate more multimedia and internet aspects. All of the facilities will have more staff and longer opening hours and therefore more student attendance. Improvement of lecturers and the teaching staff is conducted through many efforts. Internationally, more lecturers will be assigned to pursue post-graduate degrees at quality foreign schools in the near future. Domestically, the frequency of attending national conferences and workshops will be increased. Internally, the department plans to start a series of seminars and internal consultations to maintain the quality of education, formulate better methods of education, and establish a system of class notes for courses. Student output is measured in terms of the quality of graduates from the program. The quality of graduates is expected to rise as a result of the following activities in the next five years. More English based instructions and improved language lab will enable students to post higher averageTOEFL scores of 500. The ratio of student to lecturers is expected to reach 7.5 students/lecturer, leading to more concentrated classes. The average study time (coursework plus skripsi) of students is expected to drop from the current figure of 4 years and 10 month. The average cumulative GPA is expected to reach 3.3. Finally, the waiting time of graduates to enter new jobs will be reduced to 3 months after graduation. Through careful planning and execution, the goals of the department will be accomplished. The department can draw upon the resources of its teaching staff, which are among the most respected in the country, and its alumni, who are among the most prominent in the government and private sectors. Its reputation and credibility is proven in the numerous joint education and research programs it has initiated with the most important public institutions and private corporations all over the country. It also holds the distinction as one of two departments offering a doctorate program in economics in Indonesia.